2007
DOI: 10.1002/erv.848
|View full text |Cite
|
Sign up to set email alerts
|

Emotional awareness and core beliefs among women with eating disorders

Abstract: Patients with eating disorders have been shown to experience the emotional components of alexithymia-difficulties in identifying and describing emotions. In keeping with cognitive theories, which stress the role of schema-level beliefs in understanding emotions, this study examined the core beliefs that are associated with this difficulty in women with eating disorders. Seventy eating-disordered women completed standardised measures of core beliefs and alexithymia. There were no differences in alexithymia betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
5
15
0
Order By: Relevance
“…This latter point confirms recent findings by other authors 28,29. We add that the presence of purging behaviors does not appear to influence affect dysregulation, as no statistically significant differences were found among the three different groups (AN, BN, and EDNOS) on the TAS 20 scale and on its subscales.…”
Section: Discussionsupporting
confidence: 92%
“…This latter point confirms recent findings by other authors 28,29. We add that the presence of purging behaviors does not appear to influence affect dysregulation, as no statistically significant differences were found among the three different groups (AN, BN, and EDNOS) on the TAS 20 scale and on its subscales.…”
Section: Discussionsupporting
confidence: 92%
“…Within the construct of alexithymia, the affective elements (e.g., problems identifying and expressing emotional states) has been suggested as more relevant to women with EDs than the cognitive elements (e.g., poor externally oriented thinking) [24]. The current study supports this literature by suggesting that one of the reasons for employing ED behaviours may be to manage the distress associated with feeling confused by strong negative emotions.…”
Section: Discussionsupporting
confidence: 72%
“…The concern that emotions can be uncontrollable or dangerous is consistent with Wells’ identification of metacognitions that verbal thoughts can be uncontrollable or dangerous [12]. The theme of emotions being confusing is consistent with findings of higher levels of alexithymia in those with EDs [24-27]. …”
Section: Discussionsupporting
confidence: 66%
“…Higher scores reflect higher levels of associated schemata. The meta-analysis ( This reflects findings of individual studies (excluded from metaanalysis) which showed elevated levels of maladaptive schemata in ED (Overton, Selway, Strongman, & Houston, 2005) and AN samples relative to HCs (Deas, Power, Collin, Yellowlees, & Grierson, 2011;Lawson, Emanuelli, Sines, & Waller, 2008;Waller et al, 2003). Whilst some studies reported that entitlement beliefs may not be elevated in people with AN (Leung & Price, 2007;Sines, Waller, Meyer, & Wigley, 2008;Waller et al, 2003), the pooled effect suggests that such beliefs may be present, but being of small effect could be lost in individual studies with small samples.…”
Section: Beliefs and Schematamentioning
confidence: 80%
“…By including our own meta-analysis on alexithymia we sought to reduce bias when comparing effect sizes across the review, as studies in all sections were subject to the same inclusion criteria. Taylor et al, 1988) to examine alexithymia in people with AN (Beales & Dolton, 2000;Berthoz, Perdereau, Godart, Corcos, & Haviland, 2007;Corcos et al, 2000;Deborde et al, 2007;De Panfilis, Rabbaglio, Rossi, Zita, & Maggini, 2003;Franzoni et al, 2013;Lawson et al, 2008;Marchesi, Ossola, Tonna, & De Panfilis, 2014;Torres et al, 2015; Appendix A for metaanalysis references). One study used the Bermond-Vorst Alexithymia questionnaire (Vorst & Bermond, 2001) which the authors report has a total score considered equivalent to that of the TAS (Courty et al, 2013).…”
Section: Emotional Awareness and Identificationmentioning
confidence: 99%